The Existence of Tax Courts in Indonesia From the Colonial Era, Independence, to Reformation - Hanifa, Dien; Arrisman, Arrisman; Haryanto , Imam (Pelopor Publikasi Akademika, 2024)
The source of the State Budget is Taxes. Tax is a mandatory contribution that is coercive because it is regulated by law. One of the tax collection systems is self-assessment, where taxpayers are given the freedom to pay and report their taxes independently, the fiscal officer supervises and checks the tax returns reported by taxpayers every year. This difference in opinion on the results of the examination between taxpayers and tax officers is what raises the problem of tax disputes. The problem of tax disputes has existed from the Dutch colonial era to the present. The Tax Court is the body that decides tax dispute cases, the name and duties of the tax court have changed from time to time and with the decision number 26/PUU-XXI/2023 concerning the Tax Court. The authority of the tax court changed to the full authority of the Supreme Court. This article concludes that the Tax Court developed over time, and along with tax reform the Tax Court also underwent reform with the transfer of organizational, administrative, and financial coaching authority to the Supreme Court (MA). With this transfer of authority, it is hoped that the Tax Court can decide tax dispute cases fairly and have legal certainty for the parties to the dispute.